Integrating failure documentation with A3 template to improve product design quality - Zhu, Linjia (Cranfield University, 2012)
Design quality always has great impact on the competitive attribution of companies. Knowledge Management has become an important process which could help companies to accumulate the knowledge created in the past, and use it to solve the current problem and for future use. Failure Mode and Effect Analysis (FMEA) has been widely implemented as a technique for identifying potential problems, whilst A3 Thinking, has been developed by Toyota as a tool to help solve problems. However, no research exists regarding integrating these strategies for the purposes of knowledge creation, capturing and provision. This research focuses on integrating an A3 Thinking Template and FMEA-based Failure Documentation which will be used to document the problem, solve the problem, allowing knowledge creation, capturing and provision. The objectives are to: (1) Synthesise the good practices of using FMEA and A3 thinking through a literature review; (2) Analyse the role and capability of FMEA and A3 thinking in capturing and communicating knowledge to support the generation of an improved design solution; (3) Design an integration between FMEA-based Failure Documentation and the A3 Thinking template for problem solving during the design stage to support knowledge visualisation and capturing in a dynamic manner; Then develop a checklist to present the knowledge captured; (4) Validate the integration via case study on product development process in collaborating company. The proposed integration of FMEA-based Failure Documentation and A3 Thinking template has 3 stages. Firstly, problems will be documented into FMEA-based Failure Documentation template. Secondly, the A3 Thinking template with its procedure will enable users to follow the instructions to find out the solution and correct the problem. And the solution and experience in problem solving, which is the knowledge, will be generated in A3 report to be provided to users for avoiding problem recurrence in future.
Keywords: Design quality; knowledge management; problem solving; integration; visualisation; creation; capturing; provision